Magnitude, Characteristics, Maternal and Feto-Neonatal Outcomes of Obstetric Emergencies in Western Ethiopia, Nekemte, Ethiopia - Ashenafi Habte Woyessa; Jote Markos Caffo; Thanasekaran Palanichamy (Gynecology Obstetrics & Reproductive Medicine)
Objective: In Ethiopia very little or probably nothing is known about the significance of obstetric emergencies. This study was therefore aimed at assessing magnitude, characteristics, and outcomes of obstetric emergencies in western Ethiopia.